Knapping methods and techniques in the bracelets quarry of Cortijo Cevico (Loja, Granada) (Journal of Lithic Studies, 2016)
The stone bracelets are one of the most outstanding elements of personal ornaments of the ancient Neolithic in Western Mediterranean and the South of the Iberian Peninsula (5500-4800 cal. BCE). These bracelets are considered an element of cultural identity and a chronological marker of the first Neolithic societies in these areas. The study of the production processes of this ornament has brought a new approach to social relations of the early Neolithic groups of this area. The existence of specialized workshops and the circulation of these objects show the shift towards more complex social organizations. The aim of this paper is to present knapping methods and techniques carried out in the Neolithic bracelets quarry of the Cortijo Cevico. This quarry has recently been discovered and excavated, and it is the first site of its kind in the Iberian Peninsula. It is a rocky outcrop in the geological formation of Trías de Antequera, formed by dolomitic marbles. On this site we carried out the extraction works, as well as the first transformation of the knapping performs that were going to be processed as bracelets. In addition, we have applied for the first time in this paper the methodology consists on using diacritical schemes in the knapping waste of the bracelets. This methodology, along with experimentation and technical stigmas, has allowed the recognition of the techniques and methods applied to knapping dolomitic marbles and these are presented for the first time in this paper.